2019
DOI: 10.1039/c9nj03727f
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and antibacterial behaviour of nanostructured Ag@SiO2–penicillin with silver nanoplates

Abstract: Preparation of Ag@SiO2–penicillin NPs with superior synergistic and antibacterial properties against methicillin-resistant Staphylococcus aureus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 54 publications
0
14
0
Order By: Relevance
“…The wide and strong broad band with the maximum located at 1100 cm −1 is typical for asymmetric stretching vibrations of the Si–O-Si group. The absorption band at 950 cm −1 can be ascribed to the bending vibration of Si-OH group, but the peak at 800 cm −1 can be associated with the Si–O–Si symmetric stretching vibrations [ 46 , 47 ]. We also propose that the peak at 470 cm −1 corresponds to the bending of the bridging oxygen atom perpendicular to the Si-O-Si plane.…”
Section: Resultsmentioning
confidence: 99%
“…The wide and strong broad band with the maximum located at 1100 cm −1 is typical for asymmetric stretching vibrations of the Si–O-Si group. The absorption band at 950 cm −1 can be ascribed to the bending vibration of Si-OH group, but the peak at 800 cm −1 can be associated with the Si–O–Si symmetric stretching vibrations [ 46 , 47 ]. We also propose that the peak at 470 cm −1 corresponds to the bending of the bridging oxygen atom perpendicular to the Si-O-Si plane.…”
Section: Resultsmentioning
confidence: 99%
“…191 Besides providing sufficient colloidal stability, the priming species also acts to increase the affinity of the nanoplate surface for silica. 189 Examples of priming agents implemented for surface passivation include (3-aminopropyl)trimethoxysilane, 192 (3-aminopropyl)triethoxysilane, 189 (3mercaptopropyl)trimethoxysilane, 189 (3-mercaptopropyl)triethoxysilane, 189 1,3diaminopropane, 189 16-mercaptohexadecanoic acid 191,193 and polyvinylpyrrolidone. 194 Upon adsorption of a primer species, silica shell growth can then commence through the DMA-catalyzed Stöber approach with TEOS.…”
Section: Fabrication and Photoactivation Of A 'Uni-nanomolecular' Hyb...mentioning
confidence: 99%
“…194 Upon adsorption of a primer species, silica shell growth can then commence through the DMA-catalyzed Stöber approach with TEOS. 189,191,193 Alternatively, silica shells can be deposited atop of primed silver nanoplates using an aqueous solution of sodium silicate. 189,192 Construction of silica shells using sodium silicate offers a desirable advantage, that being that the resultant shells are much thinner (on the order of a few nanometers, ranging from approximately 2-5 nm depending on other conditions such as silicate concentration and reaction time), in comparison to shells produced via the TEOS-based Stöber method.…”
Section: Fabrication and Photoactivation Of A 'Uni-nanomolecular' Hyb...mentioning
confidence: 99%
“…Furthermore, releasing active Ag + ions from the SiO 2 carrier as an effective antibacterial agent would explain their highly toxic effects on tested microorganisms [ 81 ]. It also suggests that depositing or capping Ag NPs in core-shell systems increases their toxicity, enabling their stabilization and preventing the direct formation of Ag-NP aggregates [ 94 ]. These findings also follow Ahmed et al [ 95 ], who observed a significant toxicological impact of Ag NPs obtained through microwave-mediated synthesis against E. coli , P. aeruginosa , S. aureus, and K. pneumoniae .…”
Section: Biological Studiesmentioning
confidence: 99%